A CRITICAL EXAMINATION OF SHIELDING THE CYBERSPACE: A REVIEW ON THE ROLE OF AI IN CYBER SECURITY - Teja Reddy Gatla, (International Journal of Innovations in Engineering Research and Technology, 2022)
This review focuses on the critical analysis of AI’s role in cybersecurity to investigate the issues in the cybersecurity space. By utilizing synchronous and scattered sources on the topic in question, the opinion paper focuses capacity on AI-embedded technologies to enhance cybersecurity and discourage cyber-attacks making critical infrastructure impenetrable by malicious persons [1]. The paper is concerned with applying AI solutions paired with research documenting theoretical outcomes obtained from academic sources, field reports, and practical case examples. Suggestions, pros, and cons of those solutions, as well as the implications, are presented. More importantly, the paper does not only touch on the ethical and policy aspects of AI application in cyber security, but there is also a need for a detailed approach to cyber security, an approach that unites technological innovation to privacy, transparency, and accountability [1]. In contrast, the article brings attention to future developments and innovations in AI-based cybersecurity, which is a crucial need of the hour. AI evolution is seen in different aspects, such as designing complex Machine Learning algorithms till the inclusion of AI in Security Operations Centers (SOCs) and Threat Intelligence Platforms, which have prepared reliable weapons for cyber defense systems.